THE INFLUENCE ANALYSIS OF THE LEADERSHIP BEHAVIOR TOWARD WORKING SATISFACTION OF THE EMPLOYEE - Paais, Maartje; Sui, Jeky Melkianus (PEOPLE: International Journal of Social Sciences, 2018)
The scope of this Study is restricted to the review on the human resources management which is approached from the employee aspect in the organization. The use of this design is premised on the fact that questionnaire with Likert scale 1-5. The sampling technique of this study is census refers to the quantitative research method, in which all the members of the population are enumerated. The analysis method on this research use approach multiple regression analysis. The finding of the study reveals that variables of instructive, consultative, participative, and delegative behaviors have influence toward satisfaction of the employees. But instructive behavior did not significant toward working satisfaction of the employees. It was therefore recommended among others that combination of participative, consultative behaviors and delegative behaviors in leadership allows the improvement of employee satisfaction at STIA Ambon. Future studies should look further at the policy and leadership behavior models, specifically in public organizations, besides other influencing factors. The results of this study contribute to knowledge regarding the impact of leadership behavior on good work satisfaction of employee. Practically, this study can be used as a guideline for the future development and good work satisfaction.